Kamusal televizyon yayıncılığında küreselleşmenin etkileri - Çakıroğlu, Buket (My University, 2004)
Dünyayı derinden etkileyen küreselleşme kamu televizyonlarında da bir çok değişikliği beraberinde getirmiştir. Gelişmekte olan ülkelerde bu etkileri daha direkt olarak görebiliyoruz. Ülkemizin de içinde bulunduğu gelişmesini tamamlamamış ülkelerde kamu yayıncılığı ciddi ölçüde zedelenmiştir. TRT Kurumu da küreselleşmeye ayak uydurabilmek için yeniden yapılanma denemelerine girişmiş, bu nedenle Mckınsey ve Strateji-Mori firmalarına çalışmalar yaptırarak program yapılarında bazı değişikliklere gitmiştir. 1999 yılından itibaren dizi film çalışmalarına hız vererek özel televizyonlarla rekabet içine girmiştir. Bu dizi film çalışmaları sonucunda reklam pastasından daha çok pay alabilmeyi hedeflemiştir. Böylelikle asıl sorumlu olduğu kitle değişmiştir. Sermaye sahiplerinin görüşlerinin doğrultusunda reklam almaya başlamıştır. Küreselleşmenin TRT örneği üzerinden baktığımızda olumlu sonuçları olduğunu söylemek olanaklı görünmüyor. The purpose of this study is to make a research about the effects of globalization on television corporations providing public broadcasting. Television is a means of mass communication which must be considered seriously with regard to its effects. Particularly for developing countries like Turkey, the subject becomes a matter of more serious concern. In the first part of the study, the concept public broadcasting is discussed. The concept of public broadcasting has emerged as a result of classification of mass communication systems. This part deals with the economical and social infrastructure of public broadcasting. In the second part of the study, the concept of globalization is discussed. The historical andeconomical bases of globalization are dealt with in this part. In the third part of the study, the development of TRT Corporation providing public broadcasting in Turkey, is discussed. In the last part of the study, the effects of globalization on TRT are discussed. With the services obtained from McKinsey and Strateji Mori, the reorganization works carried out in TRT are dealt with in this part. And in the conclusion part, the effects of globalization on TRT are discussed in the light of all these informations.
Keywords: İletişim; Küreselleşme